Determinants of Pain and Predictors of Pain Relief after Ulnar Shortening Osteotomy for Ulnar Impaction Syndrome - Nuñez, Fiesky A., Jr.; Marquez-Lara, Alejandro; Newman, Elizabeth A.; Li, Zhongyu; Nuñez, Fiesky A., Sr. (Journal of Wrist Surgery, 2019)
Background The purpose of this study is to characterize patient- and surgery-specific factors associated with perioperative pain level in patients undergoing ulnar shortening osteotomy (USO) for ulnar impaction syndrome (UIS). We hypothesize that preoperative opiate consumption, tobacco utilization, and severity of ulnar variance will be associated with less postoperative pain relief.Methods All cases of USO between January 2010 and December 2016 for management of UIS were retrospectively reviewed. Patient demographics, smoking status, type of labor, and opioid utilization before surgery were recorded. Radiographic measurements for ulnar variance, radial tilt and inclination, as well as triangular fibrocartilage complex and distal radial-ulnar joint (DRUJ) morphology were assessed. Pre- and postoperative pain score were recorded. Regression analysis was performed to determine predictors of pain scores.Results A total of 69 patients were included for the final analysis with a mean age of 44 years (range 17–73 years). Seventeen patients reported use of daily opioid medications at the time of surgery (25%). Patients who used opioid analgesics daily, active laborers, smokers, and patients involved in worker compensation claims had significantly less pain relief after surgery. Patients with osteotomy performed at the metaphysis had significantly more pain relief than patients that had diaphyseal osteotomy. Regression analysis identified tobacco utilization and anatomic site of osteotomy as independent predictors of postoperative pain.Conclusion The results from this study identified smoking and location of osteotomy as independent predictors of postoperative pain relief. While smoking cessation is paramount to prevent delayed/nonunion it may also help improve pain relief following USO. The potential to achieve greater shortening with a metaphyseal osteotomy suggests that in addition to the mechanical unloading the carpus, pain relief after USO may also stem from tensioning the ulnar collateral ligaments of the wrist, the ECU subsheath, and the radioulnar ligaments.Level of Evidence This is a Level III, therapeutic study.
Keywords: pain predictors; postoperative pain; ulnar shortening osteotomy; ulnar impaction syndrome